2020
DOI: 10.1186/s12889-020-09153-y
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and their influences on nutrient intake, nutritional status and physical function in community-dwelling ethnically diverse older adults: a mixed-methods longitudinal study

Abstract: Background The United Kingdom population is ageing and becoming increasingly diverse; thus, it is vital to develop and implement interventions supporting this population shift. Social networks (SN) significantly impact health outcomes in later life, however relatively little is known about SN of community-dwelling ethnically diverse older adults. This study aimed to: 1) profile SN and changes in SN in this population over 8 months; 2) examine associations between SN, dietary intake, nutritional status, and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…• Social networks and their influences on dietary intake, nutritional status and physical function of community-dwelling ethnically diverse older adults: A mixed method longitudinal study [33] Adv Geriatr Med Res. 2019;1:e190005.…”
Section: Ongoing •mentioning
confidence: 99%
See 2 more Smart Citations
“…• Social networks and their influences on dietary intake, nutritional status and physical function of community-dwelling ethnically diverse older adults: A mixed method longitudinal study [33] Adv Geriatr Med Res. 2019;1:e190005.…”
Section: Ongoing •mentioning
confidence: 99%
“…The second part of this project is to corroborate the cross-sectional findings in a longitudinal design [20]. [33,34,36]. Additionally, the study sought to measure how any changes in social networks impacted on these variables throughout this time period.…”
Section: Work Package 1: Standardising Tools and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recognized that keeping relationships with society and other people, such as through social participation, is important to maintaining health in the elderly 1,2 . Previous studies have reported that a poor social network is associated with the development of dementia, decreased physical function, and undernutrition 3,4 . In Japan, the association of social participation with instrumental activities of daily living (IADL) 5 , healthy life years 6 , and death 7 have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, age-related visual impairment or manual dexterity can limit the ability to buy, prepare and enjoy healthy and nutritious foods [ 28 , 29 , 30 ]. Social conditions, such as living and eating alone, can also diminish dietary quality and the amount of consumed food [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%